Using in situ polymerisation to enhance adhesion of dissimilar materials. (January 2021) - Stojcevski, Filip; Siddique, Owais; Meric, Gaspard; Randall, James D.; Emonson, Nicholas S.; Henderson, Luke C.
Abstract: Dissimilar material bonding is a challenge constantly being considered within engineering. This paper presents a method for tailoring metal surfaces by covalently grafting polymers that are directly complimentary to their respective dissimilar material. Acrylic acid was grafted onto the surface of aluminium which was subsequently bonded to poly-lactic acid (PLA), nylon-6, and a nylon-6/carbon fiber hybrid via hot pressing. Improvements over 500% and 100% in lap shear strength were observed when bonded to Nylon-6 and Nylon-6/carbon fiber joints, respectively, while no improvements were observed for PLA. Poly (acrylic acid) grafted to the surface of A36 Steel and adhered to a commercial metal joining epoxy adhesive showed an improvement of 49% in lap shear strength. This paper shows that electro-grafting can be used to both supplement existing adhesive bonding techniques but also act as an avenue for tailoring of dissimilar material interfaces and create novel, adhesive free bonding opportunities with thermoplastics.